Antibactrial activity of Saponins extract from Lepudium aucheri boiss - Sultan, Mohammed Q.; Gusar, Sajid H.; Kredy, Husam M. (University of Thi-Qar Journal, 2019)
Saponins extract from Lepudium aucheri boiss was isolated and evaluated for antibacterial activity against gram negative and gram positive bacteria such as E.coli, Pseudomonas aeruginosa , Staphylococcus aureus , Streptococcus pneumoniae and Enterococcus faecalis. The inhibitory effect in vitro was defined to appear inhibition zone around the well . The study revealed that 75% (w/v) concentration was most activity against these pathogenic bacteria